Discourse of Pakistan's Identity under Strand of Liberal Citizenship: A Case Study of Musharraf Education Policy Reforms - Shafique Qurban (IDEA PUBLISHERS, 2020)
Keeping in view the political shifts in the wake of 9/11 incident, new social and political trends/concepts have emerged which affected the nations across the world particularly the Muslim world, wherein a wave of extremism and conservatism was seen to be set in. In consequence, Pakistan embarked upon to make reforms in the curriculum to avoid that wave. Accordingly, Musharraf government has adopted education reform under the banner of enlightened moderation and introduced curriculum to construct Pakistani nationalism in the context of liberal citizenship to curtail the issues like extremism and conservatism spread under the slogan of Islamization. This study pinpoints the overall impact of Musharraf policy changes upon curriculum and its role in the construction of liberal citizenship. This study uses secondary data in the shape of policy texts and curriculum of social studies. This study uses discourse analysis to analyse policy text and curriculum. The findings of the study have pointed out that the government has introduced modern contents such as life skills and scientific knowledge to tackle prevailing issues by removing biased and outdated contents from existing curricula. This study has recommended that effective policy measures to construct liberal citizenship should only be realized with effective implementation.